SOME WATER CHARACTERISTICS OF ESTUARIES IN INDONESIA - Uktoseya, Henk L. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1977)
This paper describes the results obtained during several hydro-oceanographical observations of some estuaries in Indonesia to provide environmental informations. It is also an attempt to make a general interpretation of the collected data, to explain or find out the physical processes acting in these regions.